Structural homology between 11 beta-hydroxysteroid dehydrogenase and Mycobacterium tuberculosis Inh-A enzyme: Dehydroepiandrosterone as a potential co-adjuvant treatment in diabetes-tuberculosis comorbidity - Hernández-Bustamante, Israel; Santander-Plantamura, Yanina; Mata-Espinosa, Dulce; Reyes-Chaparro, Andrés; Bini, Estela I.; Torre-Villalvazo, Iván; Tovar, Armando R.; Barrios-Payan, Jorge; Marquina-Castillo, Brenda; Hernández-Pando, Rogelio; Carranza, Andrea (Frontiers in Endocrinology, 2023)
Metabolic syndrome is considered the precursor of type 2 diabetes mellitus. Tuberculosis is a leading infection that constitutes a global threat remaining a major cause of morbi-mortality in developing countries. People with type 2 diabetes mellitus are more likely to suffer from infection with Mycobacterium tuberculosis. For both type 2 diabetes mellitus and tuberculosis, there is pulmonary production of anti-inflammatory glucocorticoids mediated by the enzyme 11β-hydroxysteroid dehydrogenase type 1 (11β-HSD1). The adrenal hormone dehydroepiandrosterone (DHEA) counteracts the glucocorticoid effects of cytokine production due to the inhibition of 11β-HSD1. Late advanced tuberculosis has been associated with the suppression of the Th1 response, evidenced by a high ratio of cortisol/DHEA. In a murine model of metabolic syndrome, we determined whether DHEA treatment modifies the pro-inflammatory cytokines due to the inhibition of the 11β-HSD1 expression. Since macrophages express 11β-HSD1, our second goal was incubating them with DHEA and Mycobacterium tuberculosis to show that the microbicide effect was increased by DHEA. Enoyl-acyl carrier protein reductase (InhA) is an essential enzyme of Mycobacterium tuberculosis involved in the mycolic acid synthesis. Because 11β-HSD1 and InhA are members of a short-chain dehydrogenase/reductase family of enzymes, we hypothesize that DHEA could be a substrate of InhA. Our results demonstrate that DHEA has a direct microbicide effect against Mycobacterium tuberculosis; this effect was supported by “in silico” docking analysis and the molecular dynamic simulation studies between DHEA and InhA. Thus, DHEA increases the production of pro-inflammatory cytokines in the lung, inactivates GC by 11β-HSD1, and inhibits mycobacterial InhA. The multiple functions of DHEA suggest that this hormone or its synthetic analogs could be an efficient co-adjuvant for tuberculosis treatment.